PENGARUH RELATIONSHIP MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA PUSKESMAS BIMA MAROA KABUPATEN KONAWE SELATAN - Siti Nur Aisyah; Alida Palilati; Juharsah Juharsah; Eliyanti Mokodompit; Nursaban Rommy (Jurnal Manajemen dan Kewirausahaan, 2022)
This study aims to determine whether relationship marketing and service quality affect patient satisfaction at the Bima Maroa Public Health Center, South Konawe Regency. The research used is quantitative research. Sources of data used in this study are primary data obtained by distributing questionnaires (research questionnaires) and secondary data obtained from supporting documents in the object of research, which includes an overview of the Bima Maroa Public Health Center. The number of samples taken in this study using the Slovin formula, namely 76 respondents. In this study, multiple linear regression analysis was used to solve research problems. Based on the results of research conducted using the SPSS 24 program, it shows that partially the relationship marketing variable has a positive and significant effect on patient satisfaction. Partially, the service quality variable has a positive and significant effect on the patient satisfaction variable. Simultaneously, relationship marketing and service quality have a positive and significant effect on patient satisfaction variables.